A cytoplasmically inherited barley mutant is defective in photosystem I assembly due to a temperature-sensitive defect in ycf3 splicing - Landau, A.M. (2009)
A cytoplasmically inherited chlorophyll-deficient mutant of barley (Hordeum vulgare) termed cytoplasmic line 3 (CL3), displaying a viridis (homogeneously light-green colored) phenotype, has been previously shown to be affected by elevated temperatures. In this article, biochemical, biophysical, and molecular approaches were used to study the CL3 mutant under different temperature and light conditions. The results lead to the conclusion that an impaired assembly of photosystem I (PSI) under higher temperatures and certain light conditions is the primary cause of the CL3 phenotype. Compromised splicing of ycf3 transcripts, particularly at elevated temperature, resulting from a mutation in a noncoding region (intron 1) in the mutant ycf3 gene results in a defective synthesis of Ycf3, which is a chaperone involved in PSI assembly. The defective PSI assembly causes severe photoinhibition and degradation of PSII. © 2009 American Society of Plant Biologists.